"The Fall of The Western Family" Ṭāhā 'Abd al-Raḥmān's Critical Islamic Ethics. (1st October 2018) - Abdessamad Belhaj
Abstract : Ṭāhā 'Abd al-Raḥmān is a Moroccan Islamic philosopher who has authored, so far, more than 25 books, and considered to be a leading intellectual in Morocco and one of the most important philosophers in the Arab world. Yet, he is unfamiliar to the Western scholarship of Islamic and Middle Eastern studies which can be inferred from the rare academic publications in European forums dedicated to this philosopher. Ṭāhā 'Abd al-Raḥmān offers a philosophical justification for Islamism and Islamic reformism, especially on ethical matters. He developed a particular interest in family ethics, criticizing the Western family ethics, and using his skills in dialectical argumentation to promote the authenticity of and superiority of Islamic values, knowledge, and communities; he could be considered al-Ghazzālī of his age.